Relationship between Increased Hematocrit Levels and Lowest Platelet Counts with Outcomes of Dengue Fever Patients in Children - Christine Handayani Tampubolon; Erida Manalu; Triana Paskah Dewi (Indonesian Journal of Global Health Research, 2025)
Aedes aegypti mosquitoes carry a virus that causes Dengue Hemorrhagic Fever (DHF), a disease that continues to be a major health concern in Indonesia, particularly for children. Because variations in hematocrit and platelet counts might reveal the severity of the illness, these tests are crucial for both diagnosing and tracking the progression of DHF. The purpose of this study is to create a picture of the patient demographics and to comprehend the association between hematocrit and platelet parameters and the clinical outcomes of juvenile DHF patients. Objective to determine whether there is a relationship between increased hematocrit levels and the lowest platelet count with the outcome of dengue fever patients in children at Ciracas Regional Hospital. This research was conducted through a quantitative descriptive model with a retrospective approach. Data collection was carried out through medical records of pediatric patients with DHF at Ciracas Regional Hospital in 2022-2024, including demographic data, hematocrit, platelet examination results, and patient outcomes. Data analysis through Univariate and Bivariate analysis with the C-Square test. From this research, it can be seen that the majority of patients experienced a decrease in platelets <50,000 and an increase in hematocrit values ≤20%. A significant correlation was found between low platelet levels and an increase of ≤20% in hematocrit levels with patient clinical outcomes with a p value = 0.000. An decreased in plateleft levels and an increased in hematocrited ≤20% are important indicators in determining the clinical outcomes of DHF in children. Patients can recover even with a decrease in platelet levels <50,000, allegedly due to good and appropriate medical intervention, and the low level of increase in hematocrit levels contributes to the patient's clinical outcomes.